Harry S. Elseffer papers - Elseffer, Harry S. (Harry Smith), 1857-1886.
Family correspondence, journal, an account of the signing of the U.S. treaty with Korea (1883), cruise itineraries, reports, drawings, clippings, photographs, and memorabilia relating to shipboard life and naval duty off the west coast of North America and Elseffer's vists to ports of China, Japan, Zanzibar, Cape Town, and Barbados.
In part, typewritten transcripts.
Naval officer.
Collection material in English.
Keywords: United States. -- Navy -- Officers; Warships -- United States -- Visits to foreign ports; United States. -- Navy. -- Pacific Fleet; Barbados -- Description and travel; Cape Town (South Africa) -- Description and travel; China -- Description and travel; Japan -- Description and travel; Korea -- Foreign relations -- United States; South Africa -- Description and travel; United States -- Foreign relations -- Korea; Zanzibar -- Description and travel; Naval officers